Differential effects of iodoacetamide and iodoacetate on glycolysis and glutathione metabolism of cultured astrocytes - Schmidt, Maike; Dringen, Ralf (Frontiers in Neuroenergetics, 2009)
Iodoacetamide (IAA) and iodoacetate (IA) have frequently been used to inhibit glycolysis, since these compounds are known for their ability to irreversibly inhibit the glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase (GAPDH). However, the consequences of a treatment with such thiol reagents on the glutathione (GSH) metabolism of brain cells have not been explored. Exposure of astroglia-rich primary cultures to IAA or IA in concentrations of up to 1 mM deprived the cells of GSH, inhibited cellular GAPDH activity, lowered cellular lactate production and caused a delayed cell death that was detectable after 90 min of incubation. However, the two thiol reagents differed substantially in their potential to deprive cellular GSH and to inhibit astrocytic glycolysis. IAA depleted the cellular GSH content more efficiently than IA as demonstrated by half-maximal effects for IAA and IA that were observed at concentrations of about 10 and 100 μM, respectively. In contrast, IA was highly efficient in inactivating GAPDH and lactate production with half-maximal effects observed already at a concentration below 100 μM, whereas IAA had to be applied in 10 times higher concentration to inhibit lactate production by 50%. These substantial differences of IAA and IA to affect GSH content and glycolysis of cultured astrocytes suggest that in order to inhibit astrocytic glycolysis without substantially compromising the cellular GSH metabolism, IA – and not IAA – should be used in low concentrations and/or for short incubation periods.